Late Pleistocene marginal marine ostracodes from the southeastern Atlantic coastal plain and their paleoenvironmental implications - Cronin, Thomas (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1979)
Upper Pleistocene deposits from 21 localities in Maryland, Virginia, South Carolina, North Carolina, and northern Florida yielded 77 ostracode species; virtually all are living today in brackish and marine water. Five late Pleistocene ostracode biofacies signifying lagoonal, oyster bank, estuarine, open sound, and inner sublittoral environments were delineated using Principal Coordinate Analysis. During the late Pleistocene, the Lagoonal and Oyster Bank Biofacies predominated in the Chesapeake Bay area, whereas east-central North Carolina was characterized by an Open Sound Biofacies similar to that in Pamlico Sound today. The Inner Sublittoral Biofacies was present in southeastern Virginia and along the South Carolina coast. The Estuarine Biofacies was found only in the Chesapeake Bay region. Paleoclimates were inferred by a comparison of Holocene and late Pleistocene ostracode zoogeography; apparently the climate during the late Pleistocene was as warm as, and in some areas warmer than at the same latitudes today. Ostracode species are illustrated by scanning electron photomicrographs Cyprideis margarita, Neocaudites atlan-tica, and Microcytherura norfolkensis are described as new species.